2020
DOI: 10.1530/erc-19-0054
|View full text |Cite
|
Sign up to set email alerts
|

Stem-like tumor cells involved in heterogeneous vasculogenesis in breast cancer

Abstract: Sorafenib, a small-molecule tyrosine kinase inhibitor with antiangiogenic activity, has been used in liver cancer and kidney cancer treatments. However, clinical trials with sorafenib for breast cancer were stopped in phase III due to limited efficacy. The existence of heterogeneous vasculatures involving tumor cells, such as vessel-like structures formed by vasculogenic mimicry and mosaic vessels, and their resistance to antiangiogenic therapy are thought to be a possible reason for failure of sorafenib thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 59 publications
(73 reference statements)
2
17
1
Order By: Relevance
“…Simple antiangiogenic therapy inhibits blood vessel formation alone and has no influence on the growth of tumor cells. Under this condition, the tumor cells may experience recoding to counteract with ischemia and hypoxia and then transform into tumor stem cells highly expressing VEGFR2, which is involved in the formation of heterogeneous vasculatures, reducing the antitumor effect of antiangiogenic drugs [33]. In the present study, the VM structure was not detected, and only three mosaic blood vessels were identified in the UTMD group.…”
Section: Analytical Cellular Pathologycontrasting
confidence: 56%
“…Simple antiangiogenic therapy inhibits blood vessel formation alone and has no influence on the growth of tumor cells. Under this condition, the tumor cells may experience recoding to counteract with ischemia and hypoxia and then transform into tumor stem cells highly expressing VEGFR2, which is involved in the formation of heterogeneous vasculatures, reducing the antitumor effect of antiangiogenic drugs [33]. In the present study, the VM structure was not detected, and only three mosaic blood vessels were identified in the UTMD group.…”
Section: Analytical Cellular Pathologycontrasting
confidence: 56%
“…Oestrogen regulates PEDF in the endometrium [20], ovarian surface epithelial cells [18] and granulosa cells [19]. There has only been one report indicating that PEDF expression is under the regulatory control of oestrogen in BC cells [24], but this study did not utilise a microenvironment containing other forms of oestrogen-E1 and E1S.…”
Section: Breast Cancermentioning
confidence: 93%
“…PEDF may prevent BC cell EMT by regulating nuclear factor-kappa B (NF-κB) and extracellular signal regulated kinase (ERK)/Akt signalling to decrease the expression of EMT markers vimentin, Snail, fibronectin, and matrix metalloproteinases (MMPs), and increase E-cadherin expression, an important cell adhesion molecule [25,26]. The ability of PEDF to potently inhibit tumour angiogenesis is another important anti-tumour mechanism, whereby PEDF reduces BC growth and improves survival potentially by downregulating pro-angiogenic hypoxia inducible factor (HIF)-α/α-smooth muscle actin signalling in BC cells [24]. These findings show decreased PEDF expression promotes a pro-angiogenic, pro-metastatic tumour microenvironment (TME) essential for facilitating BC growth and progression.…”
Section: Breast Cancermentioning
confidence: 99%
“…Its possible mechanism of action is related to inflammation-related pathways. A study has found that PEDF can inhibit angiogenesis from endothelial cells and tumor cells by downregulating HIF-1α in breast cancer (Mao et al, 2020). Notably, PEDF is up-regulated in the liver of cirrhotic humans and bile duct-ligated rats, and the adenovirus-mediated gene transfer in bile duct-ligated rats exogenously overexpresses PEDF, which inhibits liver angiogenesis, fibrogenesis and reduces portal pressure (Mejias et al, 2015).…”
Section: Retinal Pigment Epithelium-derived Factormentioning
confidence: 99%